2014
DOI: 10.1136/bmjopen-2014-005020
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with in-centre haemodialysis care: an international survey

Abstract: ObjectivesTo evaluate patient experiences of specific aspects of haemodialysis care across several countries.DesignCross-sectional survey using the Choices for Healthy Outcomes in Caring for End-Stage Renal Disease (CHOICE) questionnaire.SettingHaemodialysis clinics within a single provider in Europe and South America.Participants2748 adults treated in haemodialysis.Primary and secondary outcomesThe primary outcome was patient satisfaction with overall care. Secondary outcomes included patient experiences of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
1
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 54 publications
6
42
1
8
Order By: Relevance
“…This requires professionals to be aware of the need for many patients to foster relationships that enable ongoing information provision, communication, and support. A perceived lack of information sharing has been linked with reduced satisfaction with care (7,52,53). In common with other studies, this synthesis highlights problems with information sharing between health professionals and patients with CKD (6,7,52,54).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This requires professionals to be aware of the need for many patients to foster relationships that enable ongoing information provision, communication, and support. A perceived lack of information sharing has been linked with reduced satisfaction with care (7,52,53). In common with other studies, this synthesis highlights problems with information sharing between health professionals and patients with CKD (6,7,52,54).…”
Section: Discussionsupporting
confidence: 59%
“…Although there has been some reported improvement in survival in recent years (2,4), studies have shown no improvement in quality of life (3). Deficiencies in satisfaction with hemodialysis care have also been shown (5)(6)(7). Satisfaction with care is unrelated to many of the clinical outcomes prioritized by physicians, and there is increasing evidence that outcomes commonly used in research and measured by registries may not be of importance to patients (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Patients expressed positive response about good social interaction (88%) and staff interaction (99% 24 Suetonia C Palmer et al observed that as respondents the most frequently ranked and excellent was staff attention to dialysis vascular access (52% to 56%). 25 In our study, maximum (75%) numbers of patients were aware that Gua can be consumed, and then 59% were having knowledge about intake of pulses. None of them aware about almond, salted butter, Chinese salt meat, yeast products, tomato, soya sauce and cakes as a nonconsumable food items.…”
Section: Discussionmentioning
confidence: 56%
“…However, we do not typically provide "excellent education to inform modality decision making." In a large survey of .2000 patients, ,25% of patients indicated that heath care providers gave "excellent" information when choosing HD or PD (6). Other large studies also found that a significant proportion of patients (approximately 40%-65%) felt that they did not have a choice in dialysis modality or that they were not informed of their choices (7,8) (choice A is incorrect).…”
Section: Discussion Of Question 1amentioning
confidence: 99%